2010
DOI: 10.1038/emboj.2010.292
|View full text |Cite
|
Sign up to set email alerts
|

ROS-mediated amplification of AKT/mTOR signalling pathway leads to myeloproliferative syndrome in Foxo3−/− mice

Abstract: Reactive oxygen species (ROS) participate in normal intracellular signalling and in many diseases including cancer and aging, although the associated mechanisms are not fully understood. Forkhead Box O (FoxO) 3 transcription factor regulates levels of ROS concentrations, and is essential for maintenance of hematopoietic stem cells. Here, we show that loss of Foxo3 causes a myeloproliferative syndrome with splenomegaly and increased hematopoietic progenitors (HPs) that are hypersensitive to cytokines. These mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
161
3
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 134 publications
(178 citation statements)
references
References 98 publications
11
161
3
3
Order By: Relevance
“…In rat, a high-fat diet increased reactive oxygen species (ROS) production in the liver [20]. It was reported that ROS upregulates TOR mRNA expression in mouse monocytes [21]. According to these studies, it follows that lipids may affect the production of humoral compounds, cytokines, IkBa/NF-kB and TOR/ S6K1 signalling molecules in fish immune organs, and the possibility is worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In rat, a high-fat diet increased reactive oxygen species (ROS) production in the liver [20]. It was reported that ROS upregulates TOR mRNA expression in mouse monocytes [21]. According to these studies, it follows that lipids may affect the production of humoral compounds, cytokines, IkBa/NF-kB and TOR/ S6K1 signalling molecules in fish immune organs, and the possibility is worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we show that FOXO3, which is essential for the regulation of oxidative stress in HSC (12,13,21,35), is a key factor in the primitive hematopoietic cell DNA damage response, specifically in base excision repair, and it protects HSPC from oxidative DNA damage under homeostasis. These findings raise the possibility that DNA damage accrual as a result of loss of FOXO3 function, as may occur with age, promotes HSC aging (32)(33)(34), predisposes HSPCs to premature aging, and/or contributes to hematopoietic stem cell malignant transformation (18,23,29,30).…”
mentioning
confidence: 99%
“…Loss of FOXO3 results in oxidative stress-mediated myeloproliferation that does not progress, at least not rapidly enough to have been detected, toward leukemia (12,13,21). FOXO3 is intimately involved in hematopoietic malignancies, as FOXO3 is found in chromosomal translocations of human acute myeloid leukemia (22) and is inhibited in malignant hematopoietic cells (18,(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%
“…These defects can be reversed by antioxidant treatment, implicating excessive ROS production as a detrimental signal for HSCs' function and survival. [43][44][45] MTOR is a nutrient sensor that balances cell growth with nutrient availability by regulating cellular functions, including nutrient uptake, protein synthesis, and autophagy. 46 The MTOR pathway also regulates energy metabolism via transcriptional control of mitochondrial oxidative function through the YY1-PPARGC1A transcriptional complex.…”
mentioning
confidence: 99%